Long-Term Care Staff Perspectives on the Care of Persons Living With Dementia During the COVID-19 Pandemic in Sao Paulo State, Brazil - Melo, Ruth Caldeira de; Schutz, Vivian; Wachholz, Patrick Alexander [UNESP]; Villalonga-Olives, Ester; Myer, Deanna; Corazzini, Kirsten; Lepore, Michael (Slack Inc, 2023)
During the coronavirus disease 2019 (COVID-19) pandemic, the Brazilian long-term care (LTC) sector faced many challenges, which accentuated other common is-sues experienced by persons living with dementia (PLWD). The current pilot study evaluated staff perspectives regarding the care of institutionalized PLWD during the COVID-19 pandemic. Using an online survey, we collected the perspectives of 24 workers from seven long-term care facilities (LTCFs) located in Sao Paulo State, Brazil, about the impact of COVID-19 in caring for PLWD. Results highlight concerns about challenges related to following precautionary measures and the negative ef-fects of social distancing on PLWD. Aspects related to workforce and staffi ng and person-centered care approaches were recognized by staff as important to provide good care for PLWD. Future research is needed to consider how to support LTCFs in achieving a balance between the protection and well-being of PLWD. [Journal of Gerontological Nursing, 49(5), 45-52.]